Edukasi Pencegahan Stunting Pada Anak Bagi Masyarakat Kelurahan Krapyak Kota Pekalongan - Rahmadani, Anisya; Anggara, Raka; Mahrunnisa, Desy Rizky; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
Education on preventing stunting in children in the Krapyak Village community, Pekalongan City, is an important effort to improve the quality of children's health and development. Stunting, or failure to thrive due to chronic malnutrition, can have long-term impacts on children's intelligence and productivity. This educational program aims to increase public awareness and understanding of the importance of balanced nutrition, healthy eating patterns, and clean and healthy living behavior. The results of the Work Program that have been implemented are the Foster Care Program for Stunting Children, Assistance for prospective brides and grooms through the Elsimil application, Reproductive Health Counseling for Young Women, Counseling and Increasing Community Skills regarding Healthy Nutrition Menus through the Healthy Kitchen to Overcome Stunting DASHAT, Counseling and Monitoring baby growth and development , toddlers and pre-school children, Environmental Health and Sanitation Counseling, Clean and Healthy Living Behavior (PHBS). Through counseling, training and mentoring, it is hoped that the community can implement good nutritional practices, regularly monitor children's growth and access necessary health services. This education also involves various parties, including health cadres, parents and educational institutions, to create an environment that supports children's optimal growth and development, so as to reduce the prevalence of stunting in the region.